2020
DOI: 10.48550/arxiv.2006.02371
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Gamification Affects Software Developers: Cautionary Evidence from a Natural Experiment on GitHub

Lukas Moldon,
Markus Strohmaier,
Johannes Wachs

Abstract: We examine how the behavior of software developers changes in response to removing gamification elements from GitHub, an online platform for collaborative programming and software development. We find that the unannounced removal of daily activity streak counters from the user interface (from user profile pages) was followed by significant changes in behavior. Long-running streaks of activity were abandoned and became less common. Weekend activity decreased and days in which developers made a single contributi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 43 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Summarized descriptions are presented in Table 1 and Table 2. #e Moldon, Strohmaier, & Wachs [29] paper was a preprint posted to arXiv. As it had not undergone peer review, its findings were not included in that analysis; it was only used in describing the nature of studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Summarized descriptions are presented in Table 1 and Table 2. #e Moldon, Strohmaier, & Wachs [29] paper was a preprint posted to arXiv. As it had not undergone peer review, its findings were not included in that analysis; it was only used in describing the nature of studies.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Günther, Kacperski, & Krems [15] applied the same gamification feature at two different times, each for 3 months. #e timing is unknown in Moldon et al [29]. A clear research question was found in only 4/8 papers, but all stated the purposes for gamifying and studying removal.…”
Section: Nature Of Gamification Removalmentioning
confidence: 99%
See 3 more Smart Citations